2016
DOI: 10.1111/wre.12233
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Rumex obtusifolius by means of hot water

Abstract: Hot-water treatment of broad-leaved dock (Rumex obtusifolius) was developed as an alternative to manual digging out in organic farming. During treatment, the top region of the root was heated so that the plants would die back. The aim of this study was to validate the efficacy of the hot-water treatment of dock roots. The trials were carried out with a commercially available hot-water high-pressure cleaner and a rotating nozzle for water application. The target plant control rate assessed 12 weeks after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
(22 reference statements)
0
12
0
1
Order By: Relevance
“…Furthermore, soil humidity affects the time needed for seeds to reach lethal temperature (De Wilde et al 2017). Latsch et al (2017) found soil humidity to play a less important role than the water temperature and the amount of hot water. However, they found increased soil moisture to require a larger amount of hot water to reach the target control rate of bitter dock (Rumex obtusifolius L.).…”
Section: Pot Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, soil humidity affects the time needed for seeds to reach lethal temperature (De Wilde et al 2017). Latsch et al (2017) found soil humidity to play a less important role than the water temperature and the amount of hot water. However, they found increased soil moisture to require a larger amount of hot water to reach the target control rate of bitter dock (Rumex obtusifolius L.).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…could have expected better control rates than in the current experiment, which was performed in late March with moist cold soils. Furthermore, soil texture can influence the level of control for the same amount of energy applied (Latsch et al 2017). Hansson and Ascard (2002) reported a 90% reduction in the number of annual white mustard (Sinapis alba L.) plants (at their 2-leaf stage) in a field experiment with hot water (116 C just before nozzle outlet) as foliar spray at a rate of 10,000 L ha −1 (i.e., 3,970 MJ ha −1 ).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…Although this procedure presents a high success rate of 90% (Roy Latsch, Agroscope, unpublished data), it is very labour‐intensive. Effective methods aimed at damaging or removing the taproot include microwaves (Latsch et al ., ), chopping (Van Evert et al ., ), treatment with a hot steel rod (Bond et al ., ) and the application of hot water to the roots (Latsch & Sauter, ; Latsch et al ., ). Mowing or cutting can be used to control Rumex (Courtney, ; Stilmant et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This is effective but prone to mechanical failure in dry or stony soil. In the DockWeeder project, the hot water method of controlling Rumex (Latsch & Sauter, ; Latsch et al ., ) was automated (http://dockweeder.eu/ and http://ict-agri.eu/node/35755). Both methods target the taproot and consume a large amount of energy; the hot water robot additionally needs to transport a large amount of water.…”
Section: Introductionmentioning
confidence: 99%
“…The development of these principles results in trailed devices that use tractor energy, gas or hydraulic equipment to carry out tillage in rows of vineyards, berries and in areas near the trunk of fruit trees [1][2][3]. The practical application of an environmentally friendly method of removing weeds using high-pressure water jets is hampered by the lack of technical solutions to ensure compliance with the treatment regimes in field conditions [4][5]. The substantiation of the parameters of new environmentally friendly technologies and technical means to combat weed vegetation in the near-forest zone of garden plantations with an automated system of adaptation of the working body is an actual problem and has an important scientific and industrial importance.…”
Section: Introductionmentioning
confidence: 99%